Practitioners' Toolkit for Agriculture Public Expenditure Analysis - World Bank (World Bank, 2012)
This toolkit for analyzing public expenditures in agriculture contributes to a broader effort to enhance the focus, quality, and appropriate scaling of public spending in the sector. More specifically, the toolkit has two goals: to provide checklists for practitioners conducting various kinds of agriculture public expenditure analyses, and to provide selected examples on aspects of the checklist to help guide analysis. The toolkit presents a diversity of approaches and describes experiences both positive and negative in conducting agricultural public spending analyses in different settings and with different objectives. It offers checklists of issues and options, rather than a minimum list of issues to be covered. Needs, existing work time, and budget constraints will likely drive the selection of the checklist topics to be covered in any given analysis of public expenditures. The toolkit is organized to facilitate this selectivity of topic, while maintaining a strategic perspective. The supporting examples draw on numerous analyses of public expenditures in agricultures.